2019
DOI: 10.1101/608075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibiting fibroblast aggregation in skin wounds unlocks developmental pathway to regeneration

Abstract: Salamanders are capable of full-thickness skin regeneration where removal of epidermis, dermis and hypodermis results in scar-free repair. What remains unclear is whether regeneration of these tissues recapitulates the cellular events of skin development or occurs through a process unique to regenerative healing. Unfortunately, information on the post-embryonic development of salamander skin is severely lacking, having focused on compartments or cell types, but never on the skin as a complete organ. By examini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While regeneration shares mechanisms with embryonic development, the molecules involved are often different and spinal cord repair does not closely recapitulate development (Harty et al, 2003; Nacu and Tanaka, 2011; Seifert et al, 2019). A recent profiling study of peripheral nerve regeneration has found only minor correlation between the changes after peripheral axotomy and embryonic development (Renthal et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While regeneration shares mechanisms with embryonic development, the molecules involved are often different and spinal cord repair does not closely recapitulate development (Harty et al, 2003; Nacu and Tanaka, 2011; Seifert et al, 2019). A recent profiling study of peripheral nerve regeneration has found only minor correlation between the changes after peripheral axotomy and embryonic development (Renthal et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The issue of whether integrin-kindlin-driven regeneration represents a return to an embryonic pattern of expression is of obvious interest. In general, repair does not accurately recapitulate development (Harty et al, 2003; Nacu and Tanaka, 2011; Seifert et al, 2019), although basic mechanisms of cell movement are shared. In a previous study, embryonic recapitulation was marginally significant in peripheral nerve regeneration (Renthal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%